The effect of thermocycling on tensile bond strength of two soft liners. - Farideh Geramipanah; Masoumeh Ghandari; Somayeh Zeighami (Tehran University of Medical Sciences, 2013)
Failure of soft liners depends mostly on separation from the denture base resin; therefore measurement of the bond strength is very important. The purpose of this study was to compare the tensile bond strength of two soft liners (Acropars, Molloplast-B) to denture base resin before and after thermocycling.Twenty specimens fromeach of the two different soft liners were processed according to the manufacturer's instructions between two polymethyl methacrylate (PMMA) sheets. Ten specimens in each group were maintained in 37°C water for 24 hours and 10 were thermocycled (5000 cycles) among baths of 5° and 55°C. The tensile bond strength was measured using a universal testing machine at a crosshead speed of 5 mm/min. Mode of failure was determined with SEM (magnification ×30). Two-way ANOVA was used to analyze the data.The mean and standard deviation of tensile bond strength of Acropars and Molloplast-B before thermocycling were 6.59±1.85 and1.51±0.22 MPa, respectively and 5.89±1.52 and1.37±0.18 MPa, respectively after thermocycling. There was no significant difference before and after thermocycling. Mode of failure in Acropars and Molloplast-B were adhesive and cohesive, respectivley.The bond strength of Acropars was significantly higher than Molloplast-B (P